Compressive Strength and Water Absorption of Batako Made from Additional Plastic Waste of Polyethylene Terephthalate (PET) - Pratama, Romero Adi; Devi, Rida Handiana; Marwahyudi, Marwahyudi; Haryono, Yusuf Ramadhan (ASTONJADRO, 2025)
Plastic has become an inseparable material from human daily life. Plastic waste has properties that are very difficult to decompose which has a negative impact on the environment, which has become a serious problem in the global context. One alternative for dealing with plastic waste that can be applied in the world of civil engineering is by reusing plastic waste as aggregate in making bricks. This research aims to determine the effect of using polyethylene terephthalate (PET) plastic waste as a partial substitute for fine aggregate in making bricks on compressive strength and water absorption. In this research, variations in the use of PET plastic waste were 0%, 5%, 10% and 15%, referring to SNI-03-0349-1989. Compressive strength tests have respective values ​​of 7.5 Mpa, 6.3 Mpa, 6.2 Mpa, and 5.7 Mpa. In the water absorption test, the respective values ​​were 4%, 4.3%, 4.7% and 7%. Adding too much plastic to the brick mixture proved to be ineffective on the compressive strength of the brick. This means that the mortar and PET plastic on the bricks cannot interlock with each other.